Enhanced oil recovery (EOR) by ionic liquid assisted with low salinity water: Experimental study in carbonate rock - Uoda, Maraim Kh.; Hussein, Hussein Q.; Jalil, Rana R. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
There is a growing imperative to extract oil not only through primary and secondary means but also via tertiary recovery methods to meet the escalating global energy demands. Consequently, Enhanced Oil Recovery (EOR) is slated to increase significance in the oil industry in the coming years. The amalgamation of low salinity water (LSW) with chemicals to augment oil recovery has gained substantial traction in recent years owing to its demonstrated effectiveness. In this study, a systematic investigation utilizing contact angle measurements to elucidate the underlying mechanisms was undertaken. The results reveal that the contact angle (CA) demonstrated the effectiveness of the combined fluid in altering the wettability from oil-wet to water-wet. The stability of the ionic liquid C12PYCL under reservoir conditions was indicated by thermogravimetric analysis (TGA) and UV-visible spectroscopy. Following the injection of LSW for secondary recovery, core flooding tests were conducted for two different concentrations of the ionic liquid. This resulted in additional oil recoveries of 17% and 19.7% OOIP respectively, at a flow rate of 0.667 cm3/min. At the higher concentration of the ionic liquid, core flooding tests were conducted across a range of flow rates (0.334, 1, and 1.375) cm3/min, resulting in additional recoveries of 5%, 10.5%, and 8.2% OOIP. This study stands as one of the pioneering investigations in the southern oil fields of Iraq, exploring the potential of enhanced oil recovery across varying flow rates using a hybrid solution comprising LSW and ionic liquid.